The chronicle of Ibn al-Athir for the Crusading period from al-Kamil fi'l-Ta'rikh. the coming of the Franks and the Muslim response /: the coming of the Franks and the Muslim response. Years 491-541/1097-1146 : Part 1, (2017) - Unknown
No abstract available